Self-concept of Adolescent Boys Dropping Out of School and Adolescent Boys Schooling at the High School Level in Beiwali Village , Bajawa District - Yustinus Nikolaus Nango; Imelda F. E. Manurung; M. K. P. Abdi Keraf (Universitas Nusa Cendana, 2022)
Adolescents are a group of individuals aged between 10-19 years. Adolescence is considered a crucial period for individual development because, at this time, individuals experience biological, cognitive, and social transitions. Self-concept is a mental picture that a person has about himself, which includes physical and psychological images. This study aims to determine differences in self-concept between male youth who drop out of school and male adolescents attending school in Beiwali Village, Bajawa District, using a quantitative research approach with comparative techniques—testing the hypothesis in this study using the independent sample t-test. Respondents in this study amounted to 111 people consisting of 92 young men attending school and 19 male youth dropping out of school aged 15-20 people, with the sampling technique used namely probability sampling. The result of the hypothesis test is 0.011 (p <0.05), which means that there is a significant difference between the self-concept of male school dropouts and male youth attending school in Beiwali Village, Bajaw District.